1987
DOI: 10.1071/ea9870905
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between temperature and flowering in almond: effect of location

Abstract: A model for the prediction of flowering date in almond requires estimates of the chilling and heat sum requirements. We estimated hourly temperatures from daily minimum and maximum temperatures. A continuous function relating hourly temperature to rate of chilling was used to calculate daily chill unit accumulations. Heat sums were measured as growing-degree-hours: the linear accumulation of hourly temperatures above a threshold temperature. Our model was tested with estimates derived from data obtained at 1 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This behavior was already observed by Chandler and Brown (1951) when studying almond bloom in California. Another cause for blooming dispersion in almond could also be the base temperature for the fl ower bud development, which can be different not only depending on the species (Rattigan and Hill, 1987;Richardson et al, 1975), but also on the cultivars within a species, as has been observed for the progression of blooming in almond (Bernad and Socias i Company, 1995;DeGrandi-Hoffman et al, 1996;Hill et al, 1985). In addition, each cultivar could react in a different way to occasional extreme temperatures or to a sudden alternation of cold and warm temperatures, a typical phenomenon occurring during the spring in temperate climates (Couvillon and Erez, 1985;Erez and Couvillon, 1987), far away from any model of quantifi cation of chilling and heat requirements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior was already observed by Chandler and Brown (1951) when studying almond bloom in California. Another cause for blooming dispersion in almond could also be the base temperature for the fl ower bud development, which can be different not only depending on the species (Rattigan and Hill, 1987;Richardson et al, 1975), but also on the cultivars within a species, as has been observed for the progression of blooming in almond (Bernad and Socias i Company, 1995;DeGrandi-Hoffman et al, 1996;Hill et al, 1985). In addition, each cultivar could react in a different way to occasional extreme temperatures or to a sudden alternation of cold and warm temperatures, a typical phenomenon occurring during the spring in temperate climates (Couvillon and Erez, 1985;Erez and Couvillon, 1987), far away from any model of quantifi cation of chilling and heat requirements.…”
Section: Resultsmentioning
confidence: 99%
“…Heat requirements were measured as the addition of maximum and minimum daily temperatures (Tabuenca et al, 1972). Later, Rattigan and Hill (1986) applied in almond the method of Ashcroft et al (1977) and evaluated the chilling and heat requirements of 12 almond cultivars grown in the mild winter climate of Australia and also observed the infl uence of different locations on the blooming behavior of three cultivars (Rattigan and Hill, 1987). More recently, the chilling and heat requirements of 10 almond cultivars and breeding selections grown in the mild winter climate of southeastern Spain have also been reported by the assess of endodormacy breaking date by the bud weight method (Egea et al, 2003).…”
mentioning
confidence: 99%
“…In almond, a combined chill 5 unit:heat sum model based on data from one location could be used to predict anthesis time at 6 a different location with a different climate (Rattigan and Hill 1988). Winter chilling has a 7 role in flower bud initiation in Eucalyptus nitens (Gardner and Bertling 2005), and may also 8 have a role in subsequent growth and development of flower buds in E. globulus.…”
mentioning
confidence: 99%
“…Early studies on almonds and chilling accumulation resulted in requirements from 200 to 500 hours below 45°F, but this requirement varies by variety (Alonso, et al, 2003;Kester, et al, 1977;Rattigan & Hill, 1986). Rattigan and Hill (1987) claim that Nonpareil requires 340 CU while Mission requires 350 CU (Rattigan & Hill, 1987). Contrastingly, D.E.…”
Section: Bloom Timingmentioning
confidence: 99%